Why Families Go Outside: An Exploration of Mothers' and Daughters' Family-Based Nature Activities. (4th July 2022) - Izenstark, Dina; Ebata, Aaron T.
Abstract: Family-based nature activities (FBNA) are associated with improved health and family functioning, yet little research has explored how and why families spend time together outside. This study used a routine and rituals framework to explore engagement in FBNA, individual health and familial benefits, and situational and developmental constraints that influence participation. Twenty-six mothers and daughters (ages 10–12) participated in semi-structured interviews. Thematic analysis was used to analyze the data. Participation in FBNA encouraged mothers and daughters to be physically active and experience a variety of psychological benefits, including relaxation, less stress, and improved mood. The opportunity to spend time together was the most important benefit reported because it encouraged family communication, and participants reported they got along better outdoors. Weather and lack of time influenced frequency of participation, and daughters matured developmental capabilities and growing need for independence highlighted how nature-activities within families need to evolve as children age.